Appraisal of Transparency International in the Czech Republic - Kubrová, Lucie; Dvořáková, Zuzana, 1960-; Štěpánková, Marie; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2017)
This thesis aims to assess the marketing strategy and HR management done at Transparency International in the Czech Republic and to propose improvements that could help increase the awareness about the organization. To achieve this, the perception of the Czech citizens is evaluated via questionnaire. Afterwards the marketing strategy done in the Czech branch is described based on the interview with the representative of Transparency International. In the end, the individual elements are compared which enables to define improvement recommendations for the organization.
Vedoucí práce: Zuzana Dvořáková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses